2004
DOI: 10.1038/emm.2004.3
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hypotensive effect of human tissue kallikrein gene delivery and recombinant enzyme administration in spontaneous hypertension rats

Abstract: A bstractTo evaluate the feasibility of treating hypertension by hum an tissue kallikrein gene (K LK 1) delivery and by enzym e (rK1) adm inistration, tw o recombinant vectors expressing KLK1 cDNA were constructed for gene delivery (pcDNA-KLK1) and recombinant enzym e preparation (pO V-KLK1). Expression of the pcDNA-KLK1 vector in COS-1 cells was confirm ed by im m unofluorescence and in spontaneous hypertension rats (SHR) by enzymatic detection. Follow ing intram uscular or intravenous injection w ith the pcD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…These results have recently been confirmed by Sun et al [34]. Furthermore, the kallikrein gene attenuates cardiac remodeling and enhances capillary growth in SHR, through the elevation of cardiac NO, cGMP and cAMP [34]. The novel role of kallikrein/kinin, through the kinin B2 receptor, as an anti-oxidant and anti-inflammatory agent, could have further important therapeutic implications in the protection against stroke, cardiovascular and renal disease [35, 36].…”
Section: Sense To Vasodilation Genessupporting
confidence: 80%
See 1 more Smart Citation
“…These results have recently been confirmed by Sun et al [34]. Furthermore, the kallikrein gene attenuates cardiac remodeling and enhances capillary growth in SHR, through the elevation of cardiac NO, cGMP and cAMP [34]. The novel role of kallikrein/kinin, through the kinin B2 receptor, as an anti-oxidant and anti-inflammatory agent, could have further important therapeutic implications in the protection against stroke, cardiovascular and renal disease [35, 36].…”
Section: Sense To Vasodilation Genessupporting
confidence: 80%
“…Since 1997, Chao and co-workers [31,32,33] have shown that kallikrein gene delivery in SHR results in high efficiency expression and significant BP reduction. These results have recently been confirmed by Sun et al [34]. Furthermore, the kallikrein gene attenuates cardiac remodeling and enhances capillary growth in SHR, through the elevation of cardiac NO, cGMP and cAMP [34].…”
Section: Sense To Vasodilation Genessupporting
confidence: 70%
“…reduced BP in SHR but only for 3–5 days. 125 The need for repeated delivery would increase the risk of unfavourable immunologic reactions and also compromise the expected long-lasting effect. Alternative delivery systems include the use of antisense oligodeoxynucleotides and small interfering (si)RNA.…”
Section: Gene-based Therapiesmentioning
confidence: 99%